Brucella Epididymo-Orchitis: An Evaluation of Eight Cases (Annals of Medical Research, 2021)
Aim: In this study, clinical properties and treatment outcomes of 8 patients with unilateral epididymo-orchitis are evaluated.Material and Methods: A total of 8 cases were diagnosed with brucella induced epididymo-orchitis at the Urology and Infectious Diseases Clinics of Mus State Hospital within a period of 15 months. All related demographic data, clinical and laboratory findings, treatment progress and outcomes of these patients were evaluated, and the patients were followed for one year. The results obtained were statistically evaluated.Results: The mean age of the patients was 46.12 years (ranging between 20 and 58 years). The infection involvement was in the left side in five patients and in the right in three patients. All patients had applied to practitioners with acutely developing scrotal edema and pain. Systemic fever was detected in 6 (%75) patients, and Brucella spp. developed in the blood cultures of two patients. Wright agglutination test was positive in all cases. The Doppler USG examination conducted displayed ependymal cyst in two patients and testicular abscess in one. All 8 patients received antimicrobial treatment of streptomycine 1g/day for 21 days, and tetracycline 2x100mg and rifampisin 600mg/day for 6 weeks. One of the patients developed relapse due to low adherence to the treatment.Conclusion: In the endemic areas, brucella epididymo-orchitis must be considered in the possible diagnosis of the patients who apply with acutely developing scrotal pain and edema. Early diagnosis will prevent unwanted surgical interventions and complications such as infertility.